2008
DOI: 10.1002/cbic.200700590
|View full text |Cite
|
Sign up to set email alerts
|

Globotriose‐Functionalized Gold Nanoparticles as Multivalent Probes for Shiga‐like Toxin

Abstract: Compared to monovalent carbohydrates, multivalent carbohydrate ligands exhibit significantly enhanced binding affinities to their interacting proteins. Here, we report globotriose (P(k) ligand)-functionalized gold nanoparticle (AuNP) probes for the investigation of multivalent interactions with the B(5) subunit of Shiga-like toxin I (B-Slt). Six P(k)-ligand-encapsulated AuNPs (P(k)-AuNPs) of varying particle size and linker length were synthesized and evaluated for their potential as multivalent affinity probe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(83 citation statements)
references
References 73 publications
(66 reference statements)
3
77
0
2
Order By: Relevance
“…[35] The design and synthesis of multivalent ligands to block interactions between toxins and their cell-surface receptors shows potential in drug development. [36] As shown in Scheme 2, to simplify the synthetic process of Gb3, the reaction was performed in Scheme 2. A one-pot, three-enzyme system for the synthesis of globotriose.…”
Section: One-pot Enzymatic Synthesis Of Gb3 (P K ) Antigen Analogsmentioning
confidence: 99%
See 1 more Smart Citation
“…[35] The design and synthesis of multivalent ligands to block interactions between toxins and their cell-surface receptors shows potential in drug development. [36] As shown in Scheme 2, to simplify the synthetic process of Gb3, the reaction was performed in Scheme 2. A one-pot, three-enzyme system for the synthesis of globotriose.…”
Section: One-pot Enzymatic Synthesis Of Gb3 (P K ) Antigen Analogsmentioning
confidence: 99%
“…2,3,4,6-Tetra-O-acetyl-a-d-galactopyranosyl bromide 9 [33] (181 mg, 0.44 mmol), glycosyl acceptor 8 (280 mg, 0.487 mmol), silver oxide (154 mg, 0.664 mmol), and 2-aminoethyl diphenylborinate 12 [36] (22 mg, 0.1 mmol) were added to a round-bottom flask under a nitrogen atmosphere. Dry acetonitrile (10 mL) was added, and the resulting mixture was stirred at 70 8C for 2 h. The reaction mixture was filtered, and the resulting crude material was purified by silica gel chromatography (hexane/EtOAc = 3:1).…”
Section: Compoundmentioning
confidence: 99%
“…Chien et al have prepared two derivatives of P k with different chain lengths and self-assembled these onto gold nanoparticles of differing sizes (4, 13 and 20 nm). 81 These glyconanoparticles were used to assess the binding affinity towards the shiga-like toxin with the view to develop a surface plasmon resonance competition assay. The results obtained show that a longer chain length enhances the binding affinity of the P k moiety.…”
Section: Length Of the Anchor Chain That Tethers The Carbohydrate To mentioning
confidence: 99%
“…[19] Moreover, we determined that globotriose (Gb3 or blood group antigen, P k )-coated AuNPs with different particle sizes containing 60 to 1970 sugars on the surface are inhibitors of the B subunit of Shiga-like toxin (Slt-1). [25] SPR analysis revealed that the relative potencies of each sugar ranged from approximately 1300 for a 4 nm particle with a shorter linker to approximately 228 000 for a 20 nm particle with a longer linker. Thus, glyco-AuNP aggregation could be tuned for use as a newer screening method for monitoring the bond-forming activities of enzymes.…”
Section: Introductionmentioning
confidence: 99%